Integrated management strategy of contaminated soil in Peru - Díaz, Walter (2016)
Peru is a country rich in natural resources, which is not at issue but when we seek the richness of the soil resource is found that the lowest in Latin America, the relationship between man and land in our country for food production is low and limited, located only in some regions, so it is necessary to develop a strategy for integrated management of land, which starts from the ground potential, its economic, environmental and social knowledge of the possibilities, from a proper zoning, economic and ecological, categorizing their relationship to occupancy to avoid a conflict of use or benefit to our country almost always ends in socio-environmental conflicts. For example, it has contaminated soils in La Oroya, which is now a matter of legal dispute will be environmental in the arbitration against the Peruvian government before the International Centre for Settlement of Inves-tment Disputes (ICSID) for failing to decontaminate soils of La Oroya. In the case of La Oroya Antigua, is the presence of soil contaminants such as arsenic, cadmium, lead, mercury, antimony, surpassing international standards, if we compare only 393 times the arsenic exceeds international standards, then we are faced a problem that has to be addressed in a comprehensive way, not only by the presence of contaminants in soil, but also to attack and reduce or eliminate the source of generation of pollutants. In regard to pollution control of water and air have come, but has been neglected specific attention to the problem of contaminated soil, which can be seen in the lack of environmental legislation in relation to the soil and subsoil which understand from the rocky phase organic soil components. Far failed to resolve the question: What values compare national soil to see if this contaminated? Because there are no values or maximum allowable limits or standards of environmental quality, such a vacuum requires a prompt settlement of the Ministry of Environment, then all this forces us to thin in an integrated management of soils, ranging from assessment, land use planning, land management and remediation strategy to be applied to a safe environmental quality in our country.